2019
DOI: 10.1186/s12915-019-0664-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibiting eukaryotic ribosome biogenesis

Abstract: Background Ribosome biogenesis is a central process in every growing cell. In eukaryotes, it requires more than 250 non-ribosomal assembly factors, most of which are essential. Despite this large repertoire of potential targets, only very few chemical inhibitors of ribosome biogenesis are known so far. Such inhibitors are valuable tools to study this highly dynamic process and elucidate mechanistic details of individual maturation steps. Moreover, ribosome biogenesis is of particular importance fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 137 publications
0
43
0
Order By: Relevance
“…These strategies may identify molecules to target not only the increase in ribosome biogenesis observed in CRC cells but also the cancer-modified ribosomes, the recent discovery of which is owing to the tremendous progress that has recently been made to obtain high-resolution structural ribosomal features. It is compelling to find out that several molecules that were initially discovered with potent anti-CRC effects (i.e., catalpol, calcimycin, flavonoid derivatives, oxaliplatin) are target ribosome biogenesis [196]. Thus, a new phase in CRC patient management is envisioned, where characterization of ribosome biogenesis pathways together with qualitative analysis of rRNAs, will help to create personalized anticancer molecules with much less genotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…These strategies may identify molecules to target not only the increase in ribosome biogenesis observed in CRC cells but also the cancer-modified ribosomes, the recent discovery of which is owing to the tremendous progress that has recently been made to obtain high-resolution structural ribosomal features. It is compelling to find out that several molecules that were initially discovered with potent anti-CRC effects (i.e., catalpol, calcimycin, flavonoid derivatives, oxaliplatin) are target ribosome biogenesis [196]. Thus, a new phase in CRC patient management is envisioned, where characterization of ribosome biogenesis pathways together with qualitative analysis of rRNAs, will help to create personalized anticancer molecules with much less genotoxicity.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 3 , ribosome biogenesis was predicted to be the crucial biological process involving GTPBP4. Importantly, a series of studies have indicated that dysregulated ribosome biogenesis is essential for the tumorigenesis of most spontaneous cancer types and that ribosome biogenesis is closely related to tumor suppressor P53 in cell proliferation and apoptosis [ 22 24 ]. The majority of the selected target genes in the present study were also observed to participate in ribosome synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently about 100 novel inhibitors of eukaryotic ribosome formation were reported that act at different stages within the pathway [81]. Although the exact targets of these compounds are still elusive, they provide a promising toolbox to examine the eukaryotic ribosome biogenesis pathway step by step.…”
Section: Ribosome Biogenesis Inhibitors-chemical Probes To Unravel Rimentioning
confidence: 99%
“…In general, given the wealth of information already derived from the small number of specific inhibitors we have had at hand until recently, it is promising to look forward to expanding this knowledge by applying a much broader toolset. In this light, the characterization of the mode of action of the recently identified inhibitors of ribosome biogenesis [81] will have a major impact on the ribosome biogenesis research field and will pave the way for a detailed understanding of the dynamic nature of this impressive pathway.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%